2020
DOI: 10.1109/access.2020.3036131
|View full text |Cite
|
Sign up to set email alerts
|

Microgrid Energy Management System With Embedded Deep Learning Forecaster and Combined Optimizer

Abstract: and Technology. It has three components: a forecasting system, an optimizer and an optimized electrical vehicle charging station as a separate load for the system. The forecasting system is based on a deep learning model utilizing a Long Short-Term Memory (LSTM)-Autoencoder based architecture. The study provides a statistical analysis of its performance over several runs and addresses reliability and running time issues thereby building a case for its adoption. A MIDACO-MATPOWER combined optimization algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…5. The encircling behavior is depicted in (26) and (27). The exploitation and exploration of MGWO are based on grey wolf optimization and particle swarm optimization respectively.…”
Section: Modified Grey Wolf Optimization Based Emsmentioning
confidence: 99%
See 1 more Smart Citation
“…5. The encircling behavior is depicted in (26) and (27). The exploitation and exploration of MGWO are based on grey wolf optimization and particle swarm optimization respectively.…”
Section: Modified Grey Wolf Optimization Based Emsmentioning
confidence: 99%
“…The authors have also focused studies on the MG transitions between standalone and grid-connected modes and proposed a nonlinear simplex algorithm for the same [26]. V. Suresh et al analyzed the performance of a practical MG energy management system present at Wroclaw University [27]. The authors proposed a multi-objective optimization using the ant colony technique to find the best global solution.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the above-mentioned functions of the EMS are represented by means of equality and inequality constraints and in this study, they follow the constraints that are typical for AC-OPF studies. The equations are shown from (2) to (7).…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Electronics 2021, 10, x FOR PEER REVIEW 2 of 19 that enable the effective operation of the power system so that the adequate security of the energy supply is maintained and is provided at a minimum cost. In general, from review articles found in the literature [6][7][8], the EMS of a microgrid has a host of functions which are shown in Figure 1. They include data acquisition, which involves the collection of data from various elements present in the microgrid such as generators, loads, storage devices, the main grid and weather forecasts.…”
Section: Introductionmentioning
confidence: 99%
“…It has been presented as a novel study for the region under consideration. More studies in this direction involving microgrids, renewable energies and charging stations can be found in [8][9][10][11][12][13] While numerous approaches have been presented above there are still many considerations by which an optimal location of EVCSs can be obtained. Keeping in line with the sustainability motives of the present, this study presents the optimal location of an EVCS in a microgrid consisting of a significant amount of energy produced from solar panels and li-ion storage device.…”
Section: Introductionmentioning
confidence: 99%